Meneropong Cara Beragama yang Fundamentalis dan Intoleran di Indonesia melalui Pandangan Kritis Richard Rorty - Valentinus Bey (Indonesian Character Journal, 2026)
Fundamentalist and intolerant ways of practicing religion, marked by a tendency to absolutize the truth of one’s own perspective, constitute a socio-religious phenomenon that has the potential to create conflict and disintegration in communal life. Individuals who practice religion in a fundamentalist manner tend to understand their religious teachings rigidly and exclusively. This attitude leads them to reject alternative viewpoints. Indonesia, as a multi-religious country, is particularly vulnerable to this phenomenon. Many social conflicts arise because people understand and practice their religious teachings in a fundamentalistic way. In response to this issue, this paper seeks to critically examine fundamentalist ways of practicing religion based on Richard Rorty’s concept of the ironist. The aim is to discover a form of social order that is more open to religious diversity. The core of Richard Rorty’s concept of the ironist person is an awareness of human contingency, which enables individuals to refrain from claiming their beliefs and ways of life as the sole absolute truth and to remain open to recognizing what is good in others. The consequence of this perspective is an attitude of openness toward all forms of difference, fostering a richer understanding and a more tolerant way of life. This study employs a qualitative method with a library-based research approach. The findings indicate that Richard Rorty’s concept of the ironic human being is one of the concepts well suited to critiquing fundamentalist religious practices in Indonesia.